2023
DOI: 10.1002/cam4.5825
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic analysis of plain language summaries and corresponding scientific summaries of Cochrane systematic reviews about oncology interventions

Abstract: Background Cochrane plain language summaries (PLSs) are an important format to present high‐quality healthcare evidence to patients with cancer and their families. They should be written in a way everyone can understand, since they serve as a tool in decision‐making and present a bridge to overcome the gap between the healthcare users and professionals. Objective The aim of the study was to assess the language characteristics of PLSs of Cochrane systematic reviews of oncology interventions in comparison with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Although the readability of Cochrane PLSs is better than that of scientific abstracts written for medical experts 23 , there is room for improvement as the readability levels are still high above the recommended 6th grade readability level 24 . While there are studies assessing the readability of Cochrane systematic review PLSs, there is a lack of such evidence for PLSs published by organizations publishing primarily systematic reviews on social science topics.…”
Section: Introductionmentioning
confidence: 99%
“…Although the readability of Cochrane PLSs is better than that of scientific abstracts written for medical experts 23 , there is room for improvement as the readability levels are still high above the recommended 6th grade readability level 24 . While there are studies assessing the readability of Cochrane systematic review PLSs, there is a lack of such evidence for PLSs published by organizations publishing primarily systematic reviews on social science topics.…”
Section: Introductionmentioning
confidence: 99%
“…Even with existing guidance, crafting a PLS of reports that include scientific evidence and terminology may be challenging for researchers [10]. Analyses of PLSs published in Cochrane reviews found variability in their quality, readability, accuracy, and adherence to plain language recommendations [11] (i.e., Plain Language Expectations for Authors of Cochrane Summaries [PLEACS], superseded by newer Cochrane guidance [12]).…”
Section: Introductionmentioning
confidence: 99%